An Eight-Week, Web-Based Mindfulness Virtual Community Intervention for Students’ Mental Health: Randomized Controlled Trial - Ahmad, Farah; El Morr, Christo; Ritvo, Paul; Othman, Nasih; Moineddin, Rahim (JMIR Mental Health, 2020)
BackgroundInnovative interventions are needed to address the increasing mental health needs of university students. Given the demonstrated anxiolytic and antidepressant benefits of mindfulness training, we developed an 8-week, Web-based Mindfulness Virtual Community (MVC) intervention informed by cognitive behavioral therapy (CBT) constructs. ObjectiveThis study investigated the efficacy of the MVC intervention in reducing symptoms of depression, anxiety, and stress among undergraduate students in Toronto, Canada. The secondary outcomes included quality of life, life satisfaction, and mindfulness. MethodsThe first 4 weeks of the full MVC intervention (F-MVC) comprised: (1) 12 video-based modules with psycho-education on students’ preidentified stressful topics and topically applied mindfulness practice; (2) anonymous peer-to-peer discussion forums; and (3) anonymous, group-based, professionally guided, 20-min live videoconferences. The second 4 weeks of F-MVC involved access only to video-based modules. The 8-week partial MVC (P-MVC) comprised 12 video-based modules. A randomized controlled trial was conducted with 4 parallel arms: F-MVC, P-MVC, waitlist control (WLC), and group-based face-to-face CBT; results for the latter group are presented elsewhere. Students recruited through multiple strategies consented and were randomized: WLC=40; F-MVC=40, P-MVC=39; all learned about allocation after consenting. The online surveys at baseline (T1), 4 weeks (T2), and 8 weeks (T3) included the Patient Health Questionnaire-9 item, Beck Anxiety Inventory, Perceived Stress Scale, Quality of Life Scale, Brief Multi-Dimensional Students Life Satisfaction Scale, and Five-Facet Mindfulness Questionnaire. Analyses employed generalized estimation equation methods with AR(1) covariance structures and were adjusted for possible confounders (gender, age, birth country, paid work, unpaid work, physical activities, self-rated health, and mental health counseling access). ResultsOf the 113 students who provided T1 data, 28 were males and 85 were females with a mean age of 24.8 years. Participants in F-MVC (n=39), P-MVC (n=35), and WLC (n=39) groups were similar in sociodemographic characteristics at T1. At T3 follow-up, per adjusted comparisons, there were statistically significant reductions in depression scores for F-MVC (score change −4.03; P<.001) and P-MVC (score change −4.82; P<.001) when compared with WLC. At T3, there was a statistically significant reduction in anxiety scores only for P-MVC (score change −7.35; P=.01) when compared with WLC. There was a statistically significant reduction in scores for perceived stress for both F-MVC (score change −5.32; P<.001) and P-MVC (score change −5.61; P=.005) compared with WLC. There were statistically significant changes at T3 for quality of life and mindfulness for F-MVC and P-MVC vs WLC but not for life satisfaction. ConclusionsInternet-based mindfulness CBT–based interventions, such as F-MVC and P-MVC, can result in significant reductions in symptoms of depression, anxiety, and stress in a student population. Future research with a larger sample from multiple universities would more precisely test generalizability. Trial RegistrationInternational Standard Randomized Controlled Trial Number ISRCTN92827275; https://www.isrctn.com/ISRCTN92827275